Selling Our Souls: The Commodification of Hospital Care in the United States - Adam D. Reich (Princeton University Press, 2014)
The hospital has a paradoxical place in U.S. society.1 It is central to the nationâ€™s economy, yet many of us are uncomfortable with what is implied by a market for hospital care. The hospital remains a last resort for the poor and desperately sick. It is a place where most of us were born and most of us will die. And it is a place to which we often turn in our moments of greatest physical uncertainty and emotional vulnerability. We have intimate connections to hospitals and strong feelings about them. Perhaps as a result of our ambivalence about the market for hospital care, the vast amount of money that changes hands as a result of this care rarely changes hands within the hospital itself.2 As the hospital historian Rosemary Stevens observes, hospital organizations continue to â€œcarry the burden of unresolved, perhaps unresolvable contradictions.â€3 Such contradictions, between the mission of hospital care and the market for it, are the focus of this book.